RESPONSIBILITY OF DEMOGRAPHIC CHANGES IN UZBEKISTAN FOR LABOR MARKET MANAGEMENT - Najimadinov Ravshanbek Dushambaevich (Journals Park Publishing, 2022)
This article analyzed the results of the work carried out in Uzbekistan on the impact of demographic changes on the management of the rural labor market, studied and highlighted current tasks and problems. proposals and recommendations on the impact of demographic changes on rural labour market management are also given.
Keywords: labor market management process, demographic changes, birth rate